Efektivitas Teknologi OSS dalam Peningkatan Pelayanan Publik di DPMPTSP Kabupaten Pasaman Barat - Dhanny Sebastian; Aidinil Zetra; Roni Ekha Putera (PUBLICNESS: Journal of Public Administration Studies, 2025)
Online Single Submission (OSS) is a digital-based licensing system designed to simplify and accelerate public service delivery. In West Pasaman Regency, OSS is mandatory for business actors with significant investment values. However, its implementation continues to face several challenges, including low digital literacy among users, limited system integration across government agencies, and service delivery that does not meet established time standards. These issues have generated dissatisfaction and resistance from service users. This study aims to evaluate the effectiveness of OSS utilization in public service delivery at the Investment and One-Stop Integrated Service Office (DPMPTSP) of West Pasaman Regency and to identify the factors hindering its implementation. The research adopts a qualitative descriptive approach, employing in-depth interviews, documentation, and field observations. Data analysis is conducted using the Technology Acceptance Model (TAM 1) proposed by Fred Davis (1989), focusing on perceived usefulness and perceived ease of use. Informants were selected through purposive sampling, involving 14 representatives from service users and relevant government agencies. The findings reveal that OSS has not been implemented effectively. The system is perceived as providing limited benefits and being difficult to use, particularly for small business actors. These constraints have led to low levels of trust and system utilization. Enhancing OSS effectiveness requires technical improvements, increased digital literacy, and stronger institutional support.